Pola Relasi Antara Komunitas Ashram dengan Wisatawan di Ashram Ratu Bagus sebagai Daya Tarik Wisata - Chris Janitra William; Luh Putu Kerti Pujani (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
Ashram Ratu Bagus is spiritual tourist attraction located in Muncan Village, Karangasem Regency. Ashram Ratu Bagus has a spiritual teacher called Ratu Bagus and unqiue spiritual activity called Bio-Energy Meditation or Shaking Yoga difference them with other spiritual attraction. This study aims to research relationship pattern that being formed between ashram community and tourist in Ashram Ratu Bagus as tourist attraction. The research method used in this study is a qualitative and quantitative data types. Source of data that being used is primary and secondary data. Data collection techniques used are participation observation technique, unstructured interviews also document study. Informant determination using purposive sampling. Data analysis is descriptive qualitative analysis. The result of this research points out that the relationship pattern between ashram community and tourist in Ashram Ratu Bagus as tourist attraction occur because tourist want to relieve themselves, want to have serious recreation, find their trueself and interested to utilize their leisure time with spiritual education in ashram and interact with Ratu Bagus and ashram community. The relationship being formed between Ratu Bagus and tourist is teacher and student wheres Ratu Bagus as their spiritual teacher, and the relationship being formed with ashram community is familial bonds where they’re living together in same place and learning the depth of spirituality together. The relation that being formed in Ashram Ratu Bagus is a real example of potency can be created between community and tourist. Keyword: Relationship Pattern, Ashram Ratu Bagus, Tourist Attraction